PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MATERI POLA HIDUP BERGOTONG ROYONG MELALUI MODEL PEMBELAJARAN COLLABORATIVE LEARNING DI KELAS IV SDN 04 KLEGEN - Narutama, Yusril Alam; Purwandari; Setyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to improve Pancasila Education learning outcomes regarding cooperative lifestyle materials using a collaborative learning model for class IV students at SDN 04 Klegen. This type of research is Classroom Action Research (CAR). This type of research is Classroom Action Research (CAR) which is carried out in two cycles, with four stages, namely: planning; acting; observating; and reflecting. The subjects of this research were 12 students in class IV semester 2 of SDN 04 Klegen. The research results show that students' Pancasila Education learning outcomes have increased. This can be shown by the percentage of completion scores for learning Pancasila Education material on mutual cooperation lifestyle in cycle I of 41.67% or 5 out of 12 students and increasing in cycle II of 91.67%. Completeness of student learning outcomes has increased by 50%. It can be concluded that there is an increase in Pancasila education learning outcomes regarding the cooperative lifestyle material using the collaborative learning model for class IV students at SDN 04 Klegen.